Flap system power drive unit (PDU) architecture optimisation. Issue 17 (16th May 2019) - Benarous, Maamar; Panella, Isabella
Abstract : Conventional flap and slat high‐lift surfaces actuation systems in a commercial aircraft consist of actuators mechanically connected via a transmission system across the wingspan, driven from a centralised power drive unit comprising of a hydraulic, electric, or hybrid hydraulic/electric motor arrangement. The permanent coupling to the shafts makes the entire flap system move in unison, as do the slats. This paper will investigate and discuss different potential system architecture, and present the benefits associated with such architecture. It will also present the advantage that can be linked to a full electric flap configuration.